Holistic Strategy for Strengthening Religious Character and Discipline through Pancasila Student Profiles in Elementary Schools - Luqman Hakim; Yulia Santi; Rahmi Novalita (Universitas Trunodjoyo Madura, 2025)
This research aims to describe, analyze, and evaluate in-depth the implementation process of the Strengthening the Pancasila Student Profile (P3) program in an effort to optimize the formation of religious character and discipline among fifth-grade students at SD Negeri Lung Manyo, Cluster I Putroe Ijoe, Aceh Tamiang. The primary focus is to identify the specific strategies employed, the challenges encountered, and the tangible impacts on these two dimensions of student character. The study adopted a qualitative approach with a descriptive study design. Data collection was conducted through triangulation, involving intensive participatory observation within the school environment, in-depth interviews with key informants including the school principal, fifth-grade teachers, and student representatives as well as documentation analysis of lesson plans, P3 activity reports, and student discipline logs. Data validity was ensured through persistent observation and source triangulation, followed by data analysis through the stages of reduction, display, and conclusion verification. The findings significantly indicate that the implementation of P3 at SD Negeri Lung Manyo is carried out in an integrated and sustainable manner, both through intracurricular activities that embed Pancasila values and through habitual and extracurricular programs. Key strategies include routine congregational Dhuha prayers and Tadarus (Quranic recitation) to strengthen religious character, alongside the consistent implementation of a reward and punishment system in enforcing school regulations to optimize discipline. The implementation of this program has successfully yielded measurable positive impacts: students' religious character improved through increased understanding and awareness of worship practices, while student discipline improved as evidenced by better attendance rates and adherence to classroom rules. The commitment of all school stakeholders and parental support were identified as key success factors. Overall, this study concludes that strengthening the Pancasila Student Profile is not merely a program but a holistic framework that is highly effective and relevant in building a primary education ecosystem focused on superior character building. Consequently, this implementation model is recommended as a best practice for other schools.